In vitro effect of essential oils from Cinnamomum aromaticum, Citrus limon and Allium sativum on two intestinal flagellates of poultry, Tetratrichomonas gallinarum and Histomonas meleagridis - Zenner L.; Callait M.P.; Granier C.; Chauve C. (Parasite, 2003)
Essential oils may be effective preventive or curative treatments against several flagelated poultry parasites and may become primordial either to organic farms, or as more drugs are bannished. The anti-flagellate activity of essential oils obtained from fresh leaves of Cinnamomum aromaticum, Citrus limon pericarps and Allium sativum bulbs was investigated in vitro on Tetratrichomonas gallinarum and Histomonas meleagridis. On T. gallinarum, the minimal lethal concentration (MLC) at 24 hours was 0.25 μl/ml for C. aromaticum oil, and 0.125 μl/ml for C. limon and A. sativum oils. On H. meleagridis, MLC was 0.5 μl/ml for C. aromaticum oil and 1 μl/m l for C. limon and A. sativum oils at 24 and 48 hours. Moreover, no synergistic effects were evidenced in vitro. The essential oil constituents, based on their GC retention times have been also identified. The major component is trans-cinnamaldehyde (79 %) for C. aromaticum; limonene for C. limon (71 %) and diallyl tri- and disulfide (79 %) for A. sativum. Even if concentration and protocol adaptations are required for successful in vivo treatments, it appears that these oils may be useful as chemotherapeutic agents against several poultry parasites.